SPECIES COMPOSITION OF AMPHIBIAN IN GUNUNGKELIR STREAM, JATIMULYO VILLAGE, KULON PROGO - Tony Febri Qurniawan dan Trijoko (Jurnal Teknosains, 2012)
Gunungkelir stream is located in Jatimulyo village, western part of Daerah Istimewa Yogyakarta Province.The ecosystem that surrounds Gunungkelir stream looks natural and unpolluted, it is possible for good livingenvironment of amphibians. However, the database about diversity of Amphibians in Gunungkelir stream hasnot been revealed. This research was done to study species diversity, species richness, species composition anddistribution of amphibians in Gunungkelir stream as an effort to support the sustainability of amphibians livefrom extinction. The research was done on January-May 2009, at night. The VES (Visual Encounter Survey)method with line transects 250 m were used. A total 11 species of amphibians from 6 different amphibia familieswere identified. Phrynoidis aspera, Leptobrachium hasseltii and Hylarana chalconota are dominant species. Thehigest percentage of amphibians population was tadpole (38%), followed by male (35%), female (21%), and theleast were juvenile (6%). During the survey, different species of amphibians were observed with their own rangeof spatial distribution.